2022
DOI: 10.1111/jop.13320
|View full text |Cite
|
Sign up to set email alerts
|

Role of biologics in refractory recurrent aphthous stomatitis

Abstract: Refractory recurrent aphthous stomatitis (RRAS) manifests as severe ulcerative lesions of the oral mucosa with poor healing and a poor response to conventional therapy, with or without systemic diseases. Its treatment remains a clinical challenge owing to the lack of effective therapies. Recently, biologics have emerged as promising targeted therapies for RRAS. The biologics targeting specific inflammatory pathways involved in the pathogenesis of RRAS, including tumor necrosis factor-alpha inhibitors and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…According to the results of the study, patients with ATD were 1.93 times more likely to have RAS than healthy controls. Although the initiating cause and etiology of RAS are not clear, there are some studies on the coexistence of RAS and autoimmune diseases [ 11 13 ]. In a cohort study of a sample population of 1 million, Lee et al, concluded that RAS - like lesions may be an early sign of autoimmune diseases, as they were associated with an increased risk of systemic lupus erythematosus, rheumatoid arthritis, gout, ankylosing spondylitis, and Behçet’s disease [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the study, patients with ATD were 1.93 times more likely to have RAS than healthy controls. Although the initiating cause and etiology of RAS are not clear, there are some studies on the coexistence of RAS and autoimmune diseases [ 11 13 ]. In a cohort study of a sample population of 1 million, Lee et al, concluded that RAS - like lesions may be an early sign of autoimmune diseases, as they were associated with an increased risk of systemic lupus erythematosus, rheumatoid arthritis, gout, ankylosing spondylitis, and Behçet’s disease [ 13 ].…”
Section: Discussionmentioning
confidence: 99%